Soft Selling Marketing Communication Strategy Through Instagram Social Media To Achieve Millennials Market Share - Gatot Wijayanto; Jushermi Jushermi; Arwinence Pramadewi; Rovanita Rama (Eduvest - Journal of Universal Studies, 2022)
Using soft sell will cause a more positive affective response than rational appeal or hard sell so that it can increase the level of buying interest, especially share. This study aims to analyze the marketing communication strategy of soft selling through Instagram social media in achieving the millennial market share. The research method used in this study is a qualitative descriptive method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques (library study) which refers to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. The results of the study conclude that the STP strategy is an effort to achieve the maximum target market. STP (Segments, Targeting, Positioning) strategy to suit the type and purpose of the product to be marketed. The modeling that has been carried out as described in the literature study and the results and discussion has succeeded in showing the relationship between the values ​​of Engagement, New Customer, Company Total Sales, Profit, and Marketshare (market share) as evidenced by structural validation